Comparing the travel cost method and the contingent valuation method: An application of convergent validity theory to the recreational value of Irish forests - Karen Mayor; Sue Scott; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2007)
The purpose of this study is to check the monetary value of the recreational use of Irish forests using two different valuation methods on the one dataset - the Travel Cost Method and the Contingent Valuation Technique - and in doing so test convergent validity, i.e. whether they are consistent with each other. It is found that convergence cannot be established with this data. The Willingness-to-Pay for entrance responses are stationary and tend to cluster around IR1 per adult equivalent per trip. The TCM results of consumer surplus, which should be the same as WTP, are more variable depending on which sample is analysed and range between IR2.38 and IR5.95 per adult equivalent per trip. No correlation between these two variables was found. It seems that there are problems in getting people to state their true WTP. This is possibly due to a misinterpretation of the question by respondents as well as a tendency to revert to a common number. It is also likely that respondents used their WTP answers to make a political statement against the expansion of forestland using agricultural land. Finally, forests in Ireland are regarded as public goods and consequently there exists a stance among users that access to them should be free of charge, which might explain the large number of protest bids.
Keywords: 330; Contingent Valuation; Travel Cost Model; Forest Recreation; Aufforstung; Reisekostenansatz; Willingness to pay; Schätzung; Irland